2018
DOI: 10.25287/ohuiibf.310015
|View full text |Cite
|
Sign up to set email alerts
|

Üniversitelerde Hizmet Kalitesinin Servqual Analizi İle Ölçülmesi: Celal Bayar Üniversite’nde Bir Uygulama

Abstract: Üniversiteler eğitim sistemi üzerinde stratejik öneme sahiptir. Hizmet kalitesini iyileştirme ve geliştirmenin ilk aşaması, hizmet kalitesinin ölçümüdür. Örgütler, sunmuş oldukları hizmetin kalitesi hakkında ne kadar fazla doğru ve güvenilir bilgilere sahip olursa, kalitenin daha yüksek düzeylere çıkarılması noktasında daha etkin olabilirler. Bu çalışma, Celal Bayar Üniversitesi'nde hizmet kalitesinin ölçümünde SERVQUAL yöntemini kullanarak, öğrencilerin beklentilerini ve algılarını beş boyutta (fiziksel özell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…Considering students' perceptions, service quality is inadequate. This finding is similar to those obtained by Arakaya (2016), Aygün (2015), Gerşil andGüven (2018), andÖzçelik (2018). Perceived service quality is a general assessment of the character of a service provided (Twaissi & Al-Kilani, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Considering students' perceptions, service quality is inadequate. This finding is similar to those obtained by Arakaya (2016), Aygün (2015), Gerşil andGüven (2018), andÖzçelik (2018). Perceived service quality is a general assessment of the character of a service provided (Twaissi & Al-Kilani, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Bu nedenle, hizmet kalitesini değerlendirmek için bir dizi hizmet kalitesi çerçevesi kullanılmaktadır. Üniversitelerde hizmet kalitesini değerlendirmek için, bazı çalışmalarda (Gerşil & Güven, 2018;Türeli & Aytar, 2014;Yılmaz, Filiz & Yaprak, 2007) Parasuraman, Zeithaml ve Berry (1988) tarafından geliştirilen SERVQUAL (Hizmet Kalitesi) modeli kullanılmıştır. Yazarlara göre hizmet kalitesi; güvenilirlik, güvence, dokunulurluk, empati ve duyarlılık olmak üzere beş temel boyuta odaklanarak ölçülebilir (Parasuraman, Zeithaml & Berry, 1988).…”
unclassified
See 1 more Smart Citation
“…In another study conducted with the SERVQUAL scale on public universities, it was determined that public universities could not meet the service quality expectations of the students. In this study, it was observed that "Assurance" is the most important service quality dimension; "Responsiveness" was found to be the least important service dimension for students [3]. Bozbay et al (2020) aimed to determine the service quality expectation and perception of international students studying at Turkish universities.…”
Section: Service Quality In Higher Educationmentioning
confidence: 99%
“…Even though it is possible to come across studies that aim to determine the service quality of universities in Turkey (e.g. [3], [4], [5]), the service quality of universities is not evaluated from the perspective of international students too much. This side of this study renders it different from other academic studies and makes it unique.…”
Section: Introductionmentioning
confidence: 99%